Prostate Ductal Adenocarcinoma. Issue 7 (August 2018) - Amin, Ali
Abstract : Prostate ductal adenocarcinoma (PDA) is a rare subtype of prostate adenocarcinoma that shows more aggressive behavior than conventional prostatic acinar adenocarcinoma. PDA demonstrates similar clinical and paraclinical features such as prostatic acinar adenocarcinoma; therefore, clinical distinction of the 2 entities is very difficult (if not impossible) and histopathology plays an important role in the diagnosis of the disease. This review discusses all the necessary information needed for the diagnosis and prognosis of PDA including the morphologic features of PDA, an introduction about the known variants of PDA with helpful hints in grading of each variant, tips on differential diagnosis of PDA from the common morphologic mimickers, a detailed discussion on the value of immunohistochemistry in the diagnosis of PDA, and pathologic features that are helpful in determining the outcome.